The Utilization of E-Learning Model in Writing Class for University Context: Voices of the Lecturer and the Students - Khadijah Maming; Badaruddin; Sianna; Subayir Harnur (Universitas Sulawesi Barat, 2022)
This study aims to find out how is the students’ and lecturer’s voices on the utilization of E-learning in teaching writing at Universitas Muhammadiyah Parepare. E-learning can be a solution to various educational problems. In particular, the use of technology and information is actually believed to be able to improve the quality of learning, develop student skills, expand access to education and much more. The researchers intended to know how the utilization of e-learning specially in writing subject on pandemic era. It applied qualitative approach as a research design. The participants in this research are students of English education study program at Universitas Muhammadiyah Parepare. The selected samples were interviewed to get deep information about implementation of e-Learning in teaching writing. The result showed there was negative and positive responses of the students and lecturer about the implementation of e-learning specially in writing subject. The researchers concluded that the implementation of e-learning in learning writing should be considered and adapt with the lecturer, students and the environment. The lecturers have to master and has a quality before conducting an e-learning for the students specially for the content and delivering the materials so, it would make the students would not faced a difficulties thing when they learn by e-learning. Other side is the big problem of the students was bad network.